PepT1 in a coldwater marine teleost larvae- Atlantic cod: cloning and preliminary studies of expression and phylogeny - Rønnestad, I. (2014)
Epidermal growth factor (EGF) is a major trophic factor for the intestine, and supports repair and adaptation after massive enterectomy. The decrease in Gln transport which occurs after small bowel resection (SBR) is reversed by a long-term combination of EGF plus growth hormone.